1994
DOI: 10.1227/00006123-199411000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Cavernous Angiomas and Arteriovenous Malformations of the Spinal Epidural Space

Abstract: We have retrospectively studied 11 cases of solitary cavernous and arteriovenous malformations of the spinal epidural space. The acute or subacute onset of symptoms was found in all cases, with a neurological deficit in five cases. A plain x-ray study revealed abnormal calcification in one case. Hyperdensity with no iodine enhancement was found on computed tomographic scans in all cases. Magnetic resonance imaging studies showed ovoid or round lesions with isosignal and gadolinium enhancement on T1-weighted im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
5

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 22 publications
1
35
0
5
Order By: Relevance
“…Frequently the lesion is characterized by its extension, into the intervertebral foramen. 9,10,22 The rim of hypointensity resulting from haemosidirin deposits, seen in intramedullary cavernous haemangioma is not seen in epidural cavernous haemangioma. 22,23 These radiological characteristics help to distinguish cavernous haemangiomas from other lesions of the spine.…”
Section: Discussionmentioning
confidence: 99%
“…Frequently the lesion is characterized by its extension, into the intervertebral foramen. 9,10,22 The rim of hypointensity resulting from haemosidirin deposits, seen in intramedullary cavernous haemangioma is not seen in epidural cavernous haemangioma. 22,23 These radiological characteristics help to distinguish cavernous haemangiomas from other lesions of the spine.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors estimate that the hematomas come from an arterial source [16]. Graziani et al [17] thought that an epidural cavernous hemangioma could be the cause of some of these spontaneous hematomas.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to acute SSEHs, in which surgical decompression must be carried out rapidly,41112 in the rarer chronic SSEHs, the time before decompression procedures are undertaken does not seem to be critical for the recovery of neurological function and, finally, a good clinical outcome. Coz et al13 suggested that spreading of a hematoma remains possible until blood clotting has been completed.…”
Section: Discussionmentioning
confidence: 99%